2002
DOI: 10.1111/j.1749-6632.2002.tb04151.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Related to Synaptogenesis, Neuritogenesis, and MAP Kinase in Behavioral Sensitization to Psychostimulants

Abstract: The most important characteristic of behavioral sensitization to psychostimulants, such as amphetamine and cocaine, is the very long‐lasting hypersensitivity to the drug after cessation of exposure. Rearrangement and structural modification of neural networks in CNS must be involved in behavioral sensitization. Previous microscopic studies have shown that the length of dendrites and density of dendritic spines increased in the nucleus accumbens and frontal cortex after repeated exposure to amphetamine and coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 56 publications
(72 reference statements)
5
63
2
Order By: Relevance
“…Its expression within the brain is localized to discrete areas that include high expression in specific regions of the cortex and thalamus (Kwak et al 1994). Interestingly, the MKP-1 transcript is rapidly increased after both a single dose of methamphetamine and behavioral sensitization to methamphetamine in the rat prefrontal cortex (Ujike et al 2002). Its expression peaked very rapidly, at 30 min and then declined rapidly after acute administration of methamphetamine (Ujike et al 2002) similarly to what was observed with LSD in the present experiments.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Its expression within the brain is localized to discrete areas that include high expression in specific regions of the cortex and thalamus (Kwak et al 1994). Interestingly, the MKP-1 transcript is rapidly increased after both a single dose of methamphetamine and behavioral sensitization to methamphetamine in the rat prefrontal cortex (Ujike et al 2002). Its expression peaked very rapidly, at 30 min and then declined rapidly after acute administration of methamphetamine (Ujike et al 2002) similarly to what was observed with LSD in the present experiments.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the MKP-1 transcript is rapidly increased after both a single dose of methamphetamine and behavioral sensitization to methamphetamine in the rat prefrontal cortex (Ujike et al 2002). Its expression peaked very rapidly, at 30 min and then declined rapidly after acute administration of methamphetamine (Ujike et al 2002) similarly to what was observed with LSD in the present experiments. The sensitivity of MKP-1 to methamphetamine suggests that its LSD-influenced expression may be partially increased through LSD interactions at dopamine receptors, in addition to its partial effects at 5-HT 2A receptors as shown in this work (Figs 4 and 5).…”
Section: Discussionsupporting
confidence: 85%
“…Synaptophysin is an indicator of presynaptic plasticity and synaptogenesis. 13 As shown in Figures 4J through 4L, BMSC treatment significantly increased synaptophysin expression (PϽ0.05) compared with control rats.…”
Section: Morphological Changes Along the Scar Bordermentioning
confidence: 95%
“…Similar effects were observed in the prefrontal cortex. In previous studies (28,29) the effects of methamphetamine exposure on plasticity-related genes in the rat brain were examined. Such exposure resulted in increases by 20%-40% in the expression of synaptophysin mRNA in the nucleus accumbens and in prefrontal and temporal cortices within 1 day of administration.…”
Section: Methamphetamine Effectsmentioning
confidence: 99%